THE REPRODUCTIVE BIOLOGY OF HARD CLAM (MERETRIX MERETRIX) IN THE INTERTIDAL ZONE OF NAM DINH PROVINCE - Thanh, Nguyen Xuan (Vietnam Journal of Marine Science and Technology, 2014)
This study was conducted on samples collected  from October 2011 to September 2012 in the intertidal zone of Nam Dinh province. The results showed that reproductive cycle of M. meretrix was divided into 5 stages: proliferation stage, growing stage, maturation stage, breeding stage and suspensive stage. Gonad of female have light brown, gonad of male have milky white when sexually mature. The spawning season was from late April to early September and the peak of spawning occurred from mid - May to late July. During the spawning season, the sex ratio (male : female) from 0.98 to 1.11. The first size sexual maturity of the hard clam when length is 40mm. Absolute fecundity (Fa) ranged from 318,400 to 3,825,000 eggs/individual, the  average is 1,181,151 eggs/individual. Relative fecundity by body weight (Frg1) is about 22,417 eggs/gr. Relative fecundity by fresh weight (Frg2) approximate 112,620 eggs/gr. Our findings contribute information to the production artificial seed for aquaculture, conservation and sustainable development of hard clam native resources.